Research Progress on Endoplasmic Reticulum Stress-Mediated Apoptosis and Its Regulatory Mechanism on Muscle Tenderization - LI Chenlong, LUO Yulong, DONG Yushan, DU Xuerong, YAO Lili, HOU Yanru, WANG Jiayu, XU Shengyun (Shipin Kexue, 2025)
The endoplasmic reticulum is a key site for calcium storage, lipid synthesis, protein synthesis, transport and folding, and it performs several critical biological functions. Ca2+ imbalance, protein overload, and hypoxic conditions can disrupt cellular homeostasis, leading to an increase in unfolded and misfolded proteins and triggering endoplasmic reticulum stress. Prolonged endoplasmic reticulum stress not only activates the signaling pathways of protein kinase RNA-like endoplasmic reticulum kinase (PERK), inositol requiring enzyme 1 (IRE1), and activating transcription factor 6 (ATF6) within the endoplasmic reticulum, but also mediates apoptosis by participating in the activation of B cell lymphoma 2 interacting mediator of cell death (Bim) in the cytoplasm. This review covers the mechanism underlying endoplasmic reticulum overload response and describes the pathways by which the endoplasmic reticulum mediates apoptosis including the signaling sensors (PERK, IRE1, and ATF6) within the endoplasmic reticulum, the Bim pathway in the cytoplasm, and the interplay between endoplasmic reticulum stress and oxidative stress. Furthermore, this review summarizes the mechanism by which endoplasmic reticulum stress regulates muscle tenderization from four perspectives: modification of myofibrillar proteins by reactive oxygen species, Ca2+ release, apoptosis, and the anti-apoptotic effects of heat shock proteins. It is our hope that this review will provide a more comprehensive scientific basis for improving muscle tenderness.